GE_GERICHTE P/1168/2016 vom 7. März 2023 - GE Cour de justice (2023)
TORT MORAL;ACTE D'ORDRE SEXUEL AVEC UN ENFANT;VIOL;TENTATIVE(DROIT PÉNAL) | CPP.126; CO.49; CP.187.ch1; CP.189.al1; CP.190.al1; CP.22.al1; CP.191